Recruiting faculty members at the University of the Emirates for the implementation of artificial intelligence applications in the educational process: "A field study within the framework of the Unified Theory of Acceptance and Use of Technology " - Amel Anbar Bashir Bilal; Wesam Almahallawi (Arid Scientific Ltd, 2024)
International Journal of Social Sciences and Humanities Volume: 6 No: 2 (page:1-33)